Consensus on the treatment of vitiligo - Brazilian Society of Dermatology, - Gerson Dellatorre; Daniela Alves Pereira Antelo; Roberta Buense Bedrikow; Tania Ferreira Cestari; Ivonise Follador; Daniel Gontijo Ramos; Caio Cesar Silva de Castro (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Vitiligo is a muco-cutaneous, autoimmune, localized, or disseminated disease, which manifests through hypochromic or achromic macules, with loss in quality of life. The prevalence of vitiligo in Brazil was determined to be 0.54%. There is no on-label medication for its treatment. To date, no Brazilian consensus on the treatment of vitiligo had been written. Objectives: The objective of this group of Brazilian dermatologists with experience in the treatment of this disease was to reach a consensus on the clinical and surgical treatment of vitiligo, based on articles with the best scientific evidence. Methods: Seven dermatologists were invited, and each was assigned two treatment modalities to review. Each treatment (topical, systemic, and phototherapy) was reviewed by three experts. Two experts reviewed the surgical treatment. Subsequently, the coordinator compiled the different versions and drafted a text about each type of treatment. The new version was returned to all experts, who expressed their opinions and made suggestions for clarity. The final text was written by the coordinator and sent to all participants to prepare the final consensus. Results/Conclusion: The experts defined the following as standard treatments of vitiligo: the use of topical corticosteroids and calcineurin inhibitors for localized and unstable cases; corticosteroid minipulse in progressive generalized vitiligo; narrowband UVB phototherapy for extensive forms of the disease. Surgical modalities should be indicated for segmental and stable generalized vitiligo. Topical and systemic anti-JAK drugs are being tested, with promising results.